Infrastructures of Apocalypse : American Literature and the Nuclear Complex - Hurley, Jessica, (Professor of literature) (Book collections on Project MUSE., 2020)
"A new approach to the vast nuclear infrastructure and the apocalypses it produces, focusing on Black, queer, Indigenous, and Asian American literatures"--